Acesso à justiça e a (in)constitucionalidade da sucumbência no processo do trabalho após a Lei 13.467/17: - Menezes, Pedro Henrique Barreto (2020)
Law 13.467 / 17 introduced in the Consolidation of Labor Laws the payment of attorney fees, in the event of succumbence, under the terms of article 791-A. The objective of the research is to analyze whether the mentioned institute (succumbence) is ruled or not of unconstitutionality, in violation of the content of article 5, XXXV, of CF / 88 (access to justice), facing, therefore, the substantive due process, which deals with the reasonableness and proportionality that standards must have. To do so, we will discuss some guidelines that will guide the interpreter in assessing this reasonableness and proportionality. Thus, we will analyze the degree of effectiveness of the rule contained in article 5, XXXV, of CF / 88, showing its contained nature, and which therefore admits restrictions in the infraconstitutional plan. We will also deal with the legal framework that governs succumbential fees - subjective right of the lawyer with a food nature - in the light of the principle of causality. Finally, we will analyze the hyposufficiency and the principle of worker protection, highlighting the information and interpretive function of this principle, which will result not in the impossibility of collecting fees due to the succumbence, but in the way of fixing and demanding the funds. As a conclusion, comparing all these variables, it will be seen that succumbence is a necessary and appropriate measure, complying with the vectors of reasonableness and proportionality, thus not offending article 5, XXXV, of the CF / 88. The developed research used the hypothetical-deductive method, with a qualitative approach and bibliographic and documentary procedure.